PERSEPSI KELUARGA MUSLIM TERHADAP KEBERADAAN STDI IMAM SYAFI'I JEMBER - Irsan, Irsan; Mu'aziz, Farchan; Jauhar, Ghufran (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
ABSTRACT STDI Imam Syafi'i Jember is a private Islamic scientific college located in Sumbersari District, Jember, East Java. STDI Imam Syafi'i was officially established as a tertiary institution in 2010. As an inseparable part of social life, STDI Imam Syafi'i needs to know the response and perception of the surrounding community regarding its existence. This research aims to describe the perceptions of Gumuk Bago and Sumber Rejo Muslim families regarding the existence of STDI Imam Syafi'i. This research is a field study. The primary data for this research are the results of interviews with the Muslim communities of Gumuk Bago and Sumber Rejo. This research uses a quantitative descriptive observation approach. This research concluded that 80.4% of Gumuk Bago and Sumber Rejo Muslim families had a favorable perception of the existence of STDIIS and 19.6% thought it was unfavorable. Among the good things they found from STDIIS were that students had religious knowledge, were polite, friendly, said hello, often provided economic assistance, were able to socialize with the community and did not create problems in society. Then, among the bad things that people find about STDIIS is that there are still STDI students who don't socialize enough, don't maintain their manners when on the road and when riding motorbikes. Key words: Muslim Family, Gumuk Bago, Sumber Rejo, STDI Imam Syafi'i